Improved 2D intelligent driver model in the framework of three-phase traffic theory simulating synchronized flow and concave growth pattern of traffic oscillations. (August 2016) - Tian, Junfang; Jiang, Rui; Li, Geng; Treiber, Martin; Jia, Bin; Zhu, Chenqiang
Highlights: The improved 2D intelligent driver model in the framework of three-phase traffic theory is proposed. The synchronized flow and phase transition from synchronized flow to jams can be simulated. The concave growth pattern of traffic oscillations can be simulated. Abstract: This paper firstly show that 2 Dimensional Intelligent Driver Model (Jiang et al., 2014) is not able to replicate the synchronized traffic flow. Then we propose an improved model by considering the difference between the driving behaviors at high speeds and that at low speeds, which is in the framework of three-phase traffic theory. Simulations show that the improved model can reproduce the phase transition from synchronized flow to wide moving jams, the spatiotemporal patterns of traffic flow induced by traffic bottleneck, and the concave growth pattern of traffic oscillations (i.e. the standard deviation of the velocities of vehicles increases in a concave/linear way along the platoon). Validating results show that the empirical time series of traffic speed obtained from Floating Car Data can be well simulated as well.